2021
DOI: 10.3233/jcm-215564
|View full text |Cite
|
Sign up to set email alerts
|

Design of computer aided translation system for English communication language based on grey clustering evaluation

Abstract: In order to facilitate communication and communication, this paper studies the optimization of the current computer-aided translation system, and proposed a design method of English communication language computer-aided translation system based on grey clustering evaluation. By optimizing the hardware configuration and algorithm function keys of the system, the English translation mechanism of multilanguage interaction, the design idea of editing and modifying after English translation and knowledge database m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Its accessibility and familiarity could contribute to its popularity among the students. In a related study, Liang and Ma (2021) observed that students use computer-aided translation tools based on their language proficiency to enhance their translation accuracy and overcome linguistic challenges. While Google Translate may not always provide the most accurate translations, its extensive database and continuous improvement make it a reliable choice for basic translation needs.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its accessibility and familiarity could contribute to its popularity among the students. In a related study, Liang and Ma (2021) observed that students use computer-aided translation tools based on their language proficiency to enhance their translation accuracy and overcome linguistic challenges. While Google Translate may not always provide the most accurate translations, its extensive database and continuous improvement make it a reliable choice for basic translation needs.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The termbase can also be used to store and retrieve several sorts of information about the term, such as gender, definition, part of speech, use, topic field, etc., depending on the level of sophistication of the computer-aided translation tool. Additionally, some computer-aided translation applications have termbases that make it much quicker and more effective to store and retrieve multimedia resources like images, music, or video files (Liang & Ma, 2021). This is in contrast to spreadsheet programs like MS Excel.…”
Section: B Terminology Managementmentioning
confidence: 99%
“…e fuzzy evaluation index is created with the help of a fuzzy set, a standard fuzzy division of a domain, and a membership function. A fuzzy algorithm [9,10] is a fuzzy environment extension. Fuzzy algorithms represent knowledge in a more natural way for human thinking.…”
Section: Introductionmentioning
confidence: 99%